Information and reference services in hybrid libraries - Martins Damian, Ieda Pelógia; da Silva, Rafaela Carolina [UNESP]; dos Santos Neto, João Arlindo [UNESP] (Universidade Estadual de Campinas, 2021)
Introduction: To make relevant information available to its users, the library provides reference and information service, which helps, in a personalized way, users satisfy their information needs. To achieve their purposes, the library and the reference and information service need to keep up with the changes presented by the environment where they operate, which has led to the emergence, among other things, of hybrid libraries. Method: In order to verify the needs of reference and information services to be offered in hybrid libraries, a qualitative and exploratory study was carried out. A literature review was developed in specific theoretical references of both themes - reference and information service and hybrid libraries - in the scope of Information Science. Results: As results, it is pointed out that there is a need for adjustments in the reference and information service for libraries to be configured as hybrids. Conclusion: It is stated that the reference and information service is directly affected by the concept of hybrid library, which brings the need to rethink its scope and vision.
Serviço de referência e informação no contexto da hibridez em bibliotecas
Keywords: Hybrid library; Hybridity; Libraries; Reference and information service